2020
DOI: 10.1017/s1368980020000403
|View full text |Cite
|
Sign up to set email alerts
|

Current iodine nutrition status in Poland (2017): is the Polish model of obligatory iodine prophylaxis able to eliminate iodine deficiency in the population?

Abstract: Objective: The monitoring of the populations’ iodine status is an essential part of successful programmes of iodine deficiency elimination. The current study aimed at the evaluation of current iodine nutrition in school children, pregnant and lactating women as a marker of the effectiveness and sustainability of mandatory iodine prophylaxis in Poland. Design: The following iodine nutrition indicators were used: urinary iodine concentration (UIC) (all participants) and serum thyroglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
0
15
0
2
Order By: Relevance
“…A more recent (2014–2017) UK survey in 2845 adults and children showed that the median UIC exceeded 100 µg/L only in regular consumers of cow milk, whereas the median UIC was lower in consumers of alternative types of milk [ 33 ]. Finally, the study of Trofimiuk-Müldner et al on children of school age ( n = 1000) and pregnant ( n = 300) and breastfeeding women ( n = 100) living in Poland showed that the mandatory sale of iodized salt to customers in the supermarkets markedly improved the iodine status in children but was not sufficient for pregnant and breastfeeding women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent (2014–2017) UK survey in 2845 adults and children showed that the median UIC exceeded 100 µg/L only in regular consumers of cow milk, whereas the median UIC was lower in consumers of alternative types of milk [ 33 ]. Finally, the study of Trofimiuk-Müldner et al on children of school age ( n = 1000) and pregnant ( n = 300) and breastfeeding women ( n = 100) living in Poland showed that the mandatory sale of iodized salt to customers in the supermarkets markedly improved the iodine status in children but was not sufficient for pregnant and breastfeeding women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in clinical practice the trend to prescribe selenium in autoimmune thyroiditis is noticeable among physicians in Europe [34]. Although mandatory iodization of household salt in Poland has led to a sustainable optimization of iodine status in the general population, iodine supplementation is still necessary in pregnant women [35]. Poland is considered as a selenium deficient country, and this may partially explain the use of dietary supplements in clinical practice [36].…”
Section: Dietary Supplements In the Treatment Of Hypothyroidismmentioning
confidence: 99%
“…It is estimated that nearly 2 billion people in the world are at risk of IDD (Ittermann et al 2020;World Health Organization 2014). Approximately 50% of the European population is mildly to moderately I deficient (Trofimiuk-Müldner et al 2020).…”
Section: Introductionmentioning
confidence: 99%